Perancangan Sistem Informasi Manajemen Penjualan Pada Nocturnal Human Brand Berbasis Java - Muhamad Sopian; Naely Farkhatin (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
This research is motivated by several problems, namely in the data input process, sales transaction processing, and this report is still done manually, namely the recording is written in a ledger so that the data obtained is often problematic due to human error. Based on the problems that have been mentioned, the authors formulate the problem of how to design a sales information system according to the needs of Nocturnal Human Brand, and assist the finance department in making reports that are stored properly and provide fast and accurate results. To perfect the results of this research, the authors use the research method of R&D (Research and Development) or development.